2019
DOI: 10.1152/ajprenal.00539.2018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise on vascular function in nondialysis chronic kidney disease: a randomized controlled trial

Abstract: Endothelial dysfunction and arterial stiffness are nontraditional risk factors of chronic kidney disease (CKD)-related cardiovascular disease (CVD) that could be targeted with exercise. This study investigated the effect of moderate to vigorous aerobic exercise on vascular function in nondialysis CKD. In this randomized, controlled trial, 36 nondialysis patients with CKD (means ± SE, age: 58 ± 2 yr, estimated glomerular filtration rate: 44 ± 2 ml·min−1·1.73 m−2) were allocated to an exercise training (EXT) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 50 publications
3
50
0
3
Order By: Relevance
“…Blinding of participants was not possible due to the nature of exercise training. Three trials 17,32,36 showed high risks of bias related to the…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blinding of participants was not possible due to the nature of exercise training. Three trials 17,32,36 showed high risks of bias related to the…”
Section: Resultsmentioning
confidence: 99%
“…However, the review had included non-RCT studies 44,45 , and some study participants were included more than twice in the meta-analysis; this may have resulted in selection bias and the overestimation of the effect of exercise on kidney function. Some studies showed that exercise training improved vascular function, attenuated the increase in sympathetic nervous system activity, and reduced blood pressure in patients with non-dialysis CKD 17,18,28,33,35,38,44 . This supports the hypothesis that exercise training could delay the decline in kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…; Kirkman et al . ). Because integrated bursts of SSNA occur with varying widths and can contain multiple peaks, the calculation of burst frequency is not feasible (Hagbarth et al .…”
Section: Methodsmentioning
confidence: 97%
“…Cutaneous vascular conductance (CVC) was calculated as red cell flux (perfusion units; PU) divided by mean arterial pressure and expressed as a percentage of maximum vasodilatation. To account for heterogeneity in vessel density across the cutaneous vascular bed, this normalization scheme is commonly used for laser Doppler flowmeter-derived data when there are no differences in maximum vasodilatation between groups (Wardell et al 1994;Stanhewicz et al 2016;Kirkman et al 2019). Because integrated bursts of SSNA occur with varying widths and can contain multiple peaks, the calculation of burst frequency is not feasible (Hagbarth et al 1972;.…”
Section: Data and Statistical Analysismentioning
confidence: 99%
“…En un estudio se valoró el impacto del ejercicio físico en este tipo de pacientes y luego de 6 meses se comprobó que los pacientes tenían una mejor función cognitiva preservando sus funciones mentales superiores y además otro beneficio que se obtiene es el aumento en la masa muscular (24)(25)(26). Por otra parte, pacientes con Enfermedad Renal Crónica que no se sometieron a diálisis pero sí a una régimen de 12 días y realizando ejercicio aeróbico moderado obtuvieron una mejoría en su condición cardiovascular, una estabilidad de su función endotelial y la mejoría en la función microvascular sin traducir esto a una disminución de la rigidez endotelial (27).…”
Section: A Nivel De Sistema Renalunclassified